Toxicity of LY303366, an Echinocandin Antifungal, in Mice Pretreated with Glucocorticoids - Clemons, Karl V. (American Society for Microbiology, 2000)
LY303366 is a semisynthetic derivative of the echinocandin class. During preclinical studies, lethal toxicity was observed in DBA/2 mice pretreated with a cortisone acetate dose followed by treatment with LY303366 at doses ranging from 12.5 to 50 mg/kg of body weight/day given intraperitoneally (i.p.). In the cortisone-treated, uninfected controls, 90% given LY303366 at 50 mg/kg died. Deaths occurred only in steroid-treated mice. In additional experiments, uninfected DBA/2 and CD-1 mice were pretreated with different glucocorticoids. Dosages were adjusted for comparative potency with cortisone and were given at one, two, or five times the equivalent cortisone dosage of 5 mg prior to treatment with LY303366 at 25 mg/kg/day given i.p. Lethal toxicity occurred in DBA/2 mice given hydrocortisone (1× or 2×), triamcinolone (1× or 5×), and cortisone. However, no mice pretreated with 1× or 5× dexamethasone died. In CD-1 mice, deaths occurred only in those given 5× triamcinolone; three of five died 2 days after the cessation of 10 days of LY303366 treatment. The causes of the deaths and why inbred DBA/2 mice are more sensitive than outbred CD-1 mice to the combined lethal effects of LY303366 and some glucocorticoids could not be determined histologically and remain unexplained. This is the first report of this toxicity of combination glucocorticoids and LY303366. Whether a similar toxicity might apply to the other compounds in the echinocandin class of antifungals and the species specificity require additional study. In addition, the clinical relevance of these observations in steroid-treated patients to the clinical safety of LY303366 and other echinocandins needs to be determined.